Functional outcome of implant removal following fracture fixation below the level of the knee: a prospective cohort study. (April 2019) - Sanders, F. R. K.; Backes, M.; Dingemans, S. A.; Hoogendoorn, J. M.; Schep, N. W. L.; Vermeulen, J.; Goslings, J. C.; Schepers, T.
Abstract : Aims: The aim of this study was to evaluate the functional outcome in patients undergoing implant removal (IR) after fracture fixation below the level of the knee. Patients and Methods: All adult patients (18 to 75 years) undergoing IR after fracture fixation below the level of the knee between November 2014 and September 2016 were included as part of the WIFI (Wound Infections Following Implant Removal Below the Knee) trial, performed in 17 teaching hospitals and two university hospitals in The Netherlands. In this multicentre prospective cohort, the primary outcome was the difference in functional status before and after IR, measured by the Lower Extremity Functional Scale (LEFS), with a minimal clinically important difference of nine points. Results: A total of 179 patients were included with a median age of 50 years (interquartile range (IQR) 37 to 60), of whom 71 patients (39.7%) were male. With a median score of 60 before IR (IQR 45 to 72) and 66 after IR (IQR 51 to 76) on the LEFS, there was a statistically significant improvement in functional outcome (p < 0 .001). A total of 31 surgical site infections (17.3%) occurred. Conclusion: Although IR led to a statistically significant improvement of functional outcome, the minimal clinically important difference was not reached. In conclusion, this study shows that IR does not result in a clinically relevant improvement in functional outcome. These results, in combination with the high complication rate, highlight the importance of carefully reviewing the indication for IR. Cite this article: Bone Joint J 2019;101-B:447–453.